2013
DOI: 10.11118/actaun201361041191
|View full text |Cite
|
Sign up to set email alerts
|

Consumers behaviour of students when shopping for organic food in the Czech Republic

Abstract: Organic farming and organic food are terms that attract the attention of not only farmers, but also economists. It is paper, which could address many consumers in the future. A healthier way of life is becoming more and more popular. This paper primarily aims to collect basic knowledge of organic farming, organic food and its labelling. Furthermore, according to conducted marketing research (1.289 respondents were addressed in questionnaire survey), it is aim to characterize the factors that influence responde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…A higher proportion of students already consume organic food, with reports of frequent consumption ranging from 44% [ 57 ] to 89%, [ 58 ]; seasonal and local food products, reported as the top SFC behaviours by Kamenidou et al [ 51 ] with mean scores of 5.46 and 5.10 out of 7, respectively; avoid some meats (47.4%) [ 26 ] or avoided plastic bottled water (34%) [ 47 ]. This contrasts with the relatively lower prevalence of self-declared “flexitarians” (15.4%) [ 33 ], “pescovegetarians” (11.6%) [ 33 ], “semi-vegetarians,” 6% [ 29 ] to 12.1% [ 33 ], vegetarians, ranging from 3.9% [ 26 ] to 25% [ 59 ], and vegans, ranging from 0.4% [ 26 ] to 1.8% [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher proportion of students already consume organic food, with reports of frequent consumption ranging from 44% [ 57 ] to 89%, [ 58 ]; seasonal and local food products, reported as the top SFC behaviours by Kamenidou et al [ 51 ] with mean scores of 5.46 and 5.10 out of 7, respectively; avoid some meats (47.4%) [ 26 ] or avoided plastic bottled water (34%) [ 47 ]. This contrasts with the relatively lower prevalence of self-declared “flexitarians” (15.4%) [ 33 ], “pescovegetarians” (11.6%) [ 33 ], “semi-vegetarians,” 6% [ 29 ] to 12.1% [ 33 ], vegetarians, ranging from 3.9% [ 26 ] to 25% [ 59 ], and vegans, ranging from 0.4% [ 26 ] to 1.8% [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies were focused on consumption of organic food (OF) [ 32 , 34 , 40 , 57 , 58 , 60 ]. Three articles reported that knowledge and attitudes about OF had a positive relationship with the purchase and consumption of these foods (Correlation coefficients (r) between 0.24 and 0.28) [ 32 , 34 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…It must address especially young people to buy organic food more and more frequently, because young people are potential customers for many years (Zámková, Prokop, 2013).…”
Section: Slovak Republicmentioning
confidence: 99%
“…As a result, the behaviour of the younger generation, which will very quickly be of productive age and become the new purchasing force, has received little investigation. In the Czech Republic, it is more obvious, because there has only been one study on the behaviour of this sector (see Zámková and Prokop, 2013). For this reason, we decided to focus our research on identifying the factors behind the consumer behaviour of the younger generation.…”
Section: Introductionmentioning
confidence: 99%